A Review of Extracorporeal Blood Purification Techniques for the Treatment of Critically Ill Coronavirus Disease 2019 Patients. Issue 10 (13th April 2022) - Niazi, Nicholas S.; Nassar, Tareq I.; Stewart, Ian J.; Honore, Patrick M.; Sharma, Kumar; Chung, Kevin K.
Abstract : In late 2019, a novel betacoronavirus, later termed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was discovered in patients with an unknown respiratory illness in Wuhan, China. SARS-CoV-2 and the disease caused by the novel coronavirus, coronavirus disease 2019 (COVID-19), spread rapidly and resulted in the World Health Organization declaring a pandemic in March 2020. In a minority of patients infected with SARS-CoV-2, severe illness develops characterized by a dysregulated immune response, acute respiratory distress syndrome, and multisystem organ failure. Despite the development of antiviral and multiple immunomodulatory therapies, outcomes of severe illness remain poor. In response, the Food and Drug Administration in the United States authorized the emergency use of several extracorporeal blood purification (EBP) devices for critically ill patients with COVID-19. Extracorporeal blood purification devices target various aspects of the host response to infection to reduce immune dysregulation. This review highlights the underlying technology, currently available literature on use in critically ill COVID-19 patients, and future studies involving four EBP platforms: 1) oXiris filter, 2) CytoSorb filter, 3) Seraph 100 Microbind blood affinity filter, and 4) the Spectra Optia Apheresis System with the Depuro D2000 Adsorption Cartridge.